TRANSPARANSI PADA LAYANAN PERUSAHAAN ASURANSI KESEHATAN DITINJAU DARI ASPEK HUKUM PERLINDUNGAN KONSUMEN - Fuad Dicky Hutagalung (Fakultas Hukum Universitas Sebelas Maret, 2024)
This article aims to examine the importance of transparency in health insurance company services from the perspective of consumer protection law. This research is a doctrinal research that studies the purpose of law, the values of justice, the validity of legal rules, legal concepts and legal norms. The results showed that health services are very important basic needs and human rights of every individual. The quality of health services has a significant effect on the degree of public health. Access to quality and affordable health services is a must, with information transparency as the main indicator. This transparency is important to increase consumer efficiency in choosing products and to increase loyalty to certain products. The Consumer Protection Law (Law No. 8 of 1999) and the Insurance Law regulate the obligations of insurance companies in providing accurate and complete information, as well as ensuring fairness in the claims process and handling consumer complaints Insurance companies must manage premium funds wisely and transparently, and engage and educate consumers about their rights. Open and transparent communication with consumers is essential to build trust. Consumer protection can also be enhanced through cooperation between the government, insurance companies, healthcare providers, and consumer organizations. By consistently carrying out these obligations, the healthcare and insurance industries can build a good reputation and gain the trust of the public.